Differences in Hypertension Risk Factors Between Coastal and Non-Coastal Communities in Kolaka Regency - Musfikayana Musfikayana; Sunarsih Sunarsih; Rahmawati Rahmawati (Waluya The International Science of Health Journal, 2026)
Introduction: Based on data on hypertension cases at the Watubangga Community Health Center, there were 1,022 cases (54%) in 2022, 1,183 cases (65%) in 2023, and 1,789 cases (91%) in 2024. Meanwhile, at the Kolaka Community Health Center in 2022, there were 4,503 cases (59%), 7,013 cases (91%) in 2022, and 9,955 cases (95%) in 2024. This study aims to analyze Differences in Hypertension Risk Factors Between Coastal and Non-Coastal Communities in Kolaka Regency. Method: This research is a comparative study. The population consisted of 325 hypertension patients registered at the Kolaka Community Health Center and Watubangga Community Health Center. Systematic random sampling was used, with 75 respondents. The statistical tests used were the chi-square test, the Mann-Whitney test, and logistic regression. Result: This study shows that there are differences in risk factors for caffeinated drinks with a P-value of 0.000 and a Mann-Whitney test of 0.000. Risk factors for salty foods with a P-value of 0.003 and a Mann-Whitney test of 0.003. Conclusion: Community health centers need to carry out promotive and preventive efforts by utilizing the Integrated Non-Communicable Disease Development Post activities as an opportunity to approach the community, especially regarding hypertension risk factors.